2008
DOI: 10.1111/j.1399-0012.2008.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of transplant renal artery stenosis managed conservatively or by radiological intervention

Abstract: The natural history and optimal treatment of transplant renal artery stenosis (TRAS) is poorly defined. Few studies reported long-term clinical outcomes. A single centre analysis of 43 patients diagnosed with TRAS 1990-2003 was performed. Twenty-seven had percutaneous intervention (including 10 patients who had >1 intervention) and 16 were managed conservatively at the discretion of the attending clinicians. Transplant function was assessed by slope of estimated glomerular filtration rate (eGFR) over five yr o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…A consensus regarding the management of TRAS remains elusive due to a lack of good quality published data, with some authors advocating intervention with percutaneous transluminal angioplasty (PTA) with or without endovascular stenting [4], whilst others recommend a more conservative approach [5].…”
Section: Introductionmentioning
confidence: 99%
“…A consensus regarding the management of TRAS remains elusive due to a lack of good quality published data, with some authors advocating intervention with percutaneous transluminal angioplasty (PTA) with or without endovascular stenting [4], whilst others recommend a more conservative approach [5].…”
Section: Introductionmentioning
confidence: 99%
“…There is significant variability in the reported incidence of TRAS (1-25%) likely secondary to institutional variation of screening protocols, thresholds for intervention and baseline patient demographics (1)(2)(3)(4)(5)(6)(7)(8). The management of TRAS is more widely agreed upon with endovascular intervention (EVI) playing a significant role in preserving graft function and prolonging graft survival (1,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term graft survival was significantly lower in the TRAS group compared to controls. However, in a study of 43 patients with TRAS (27 transplant recipients had PTA and 16 were managed conservatively), Geddes et al [5] found that there was no significant difference in the rate of deterioration in renal function or in blood pressure or number of antihypertensive agents between the groups at any time point. In their retrospective single-center study, 5 transplants in the intervention group failed (including 2 as a direct result of intervention) and 1 in the conservative group failed.…”
Section: Introductionmentioning
confidence: 99%